Evaluation of depression comorbidity in obstructive sleep apnea syndrome - Berk, Sule Sirin; Baykara, Sema (Taylor & Francis Ltd, 2019)
BACKGROUND: Diagnosis and treatment of the comorbid depression in patients with obstructive sleep apnea syndrome could be effective on the reduction of morbidity and mortality. OBJECTIVES: The present study aimed to investigate the depression comorbidity in OSAS patients grouped by Apnea-Hypopnea Index (AHI). However, the previous studies on the presence of depression in OSAS reported inconsistent findings. It was considered that the differences between the findings could be due to methodological differences and it was planned to investigate the presence of depression with two methodologies in the same patient group and to compare the findings. METHODS: The study group included 101 individuals who were admitted to the neurology outpatient clinic with the complaints of snoring, diaphoresis history, daytime somnolence, fatigue, and headache and were hospitalized overnight to conduct polysomnography and diagnosed with obstructive sleep apnea syndrome (OSAS). Cases were grouped based on Apnea-Hypopnea Index (AHI) scores. Sociodemographic and Clinical Data Form Hamilton Rating Scale for Depression (HAM-D), Beck Depression Inventory (BDI), Pittsburg Sleep Quality Index (PSQI) and Epworth Somnolence Scale (ESS) were applied to all cases. RESULTS: Patients with lower than 5 AHI score were considered as the simple snoring group (n = 20), those with an AHI score of 5-14.99 (n = 27) were considered as the patients with moderate OSAS and those with an AHI score of equal to or greater than 30 (n = 34) were considered as severe OSAS patients. The cases included in the study had a wide age range (between 22-61 years) and were mostly male (65.4% male; 34.65% female). Rates of the major depressive disorder according to HAM-D and BDI were 60.4% and 36.6%; respectively. The depression rates were higher in the moderate OSAS group according to the both evaluation methods (HAM-D and BDI), although this was not significant via BDI. Analysis of the ESS scores demonstrated that experienced severe daytime somnolence was seen in 52.5%, and analysis of the PSQI demonstrated that poor sleep quality was seen in 87.1% of the patients. According to the linear regression analysis only PSQI total score (p = 0.029) was found to be significant in determining BDI while ESS (p = 0.44) and PSQI total scores (p = 0.003) were found to be significant in determining HAM-D when ESS, AHI and PSQI were evaluated together. CONCLUSION: In patients with obstructive sleep apnea syndrome, comorbid depression should be identified in order to achieve better results in treatment. However, the scales used to determine depression in OSAS patients could result in different findings due to methodological differences or the distribution of the tested symptoms. Considering this fact in the diagnosis of comorbid depression in OSAS is important to achieve an accurate diagnosis and commence an effective treatment.
Keywords: Obstructive sleep apnea syndrome; depression; survey